Efektifitas Penggunaan Video Pembelajaran Geografi Kelas X IIS Man 1 Makassar pada Pokok Bahasan Dinamika Hidrosfer - Mustakim, Mustakim (LaGeografia, 2019)
This study aims: (1) To Know the Effectiveness of the Use of Video in Learning Geography Class X IIS MAN 1 Makassar on the Subjects of Hydrosphere Dynamics. (2) To find out the evaluation results obtained by students of Class X IIS MAN 1 Makassar with the use of video in geography learning on the subject of hydrosphere dynamics. This research is an experimental study with a research design using the pretest-posttes control group design method. The subject of this study consisted of an experimental group that used video and control groups without using video. The population in this study were all students of class X IIS MAN 1 Makassar. Determination of the sample in this study using a positive sampling method with the type of sampling nonprobability sampling, sampling is done by giving written text to all students of class X IIS MAN 1 Makassar to find the average value of two classes that are relatively the same, so the sample is class X IIS 1 and class X IIS IV. The source of the data used is the learning outcomes of both classes before treatment (pretest) and learning outcomes of both classes after treatment (posttest). Data analysis techniques used are descriptive analysis techniques and inferential analysis techniques using the T-test formula, namely the formula of the independent sample test.The results showed that: (1) the use of video in geography learning was effective to increase the knowledge of students in class X IIS MAN 1 Makassar by referring to the results of the calculation of the T-test of the experimental class and the control class in which the value of tcount was greater than the value of t table, namely (3,595>1,66691). (2) Based on the average value (mean) after the final test (posttest), the evaluation results obtained by the experimental class students who use video in geography learning on the topic of hydrosphere dynamics are 75.93. From these data it can be concluded that the use of effective learning videos is used to improve the geography of pesetas students rather than not using videos.